Analysis of Work Motivation and Compensation on PT Berlian Anugrah Jaya Employee Performance - Aryata, I Made; Tua, Rudy Bodewyn Mangasa; Manik, Corneelia Drumaya (PT FORMOSA CENDEKIA GLOBAL, 2024)
The purpose of this research is to determine the influence of Motivation and Compensation on Employee Performance at PT. Anugrah Jaya Diamonds both partially and simultaneously. The method used is a quantitative method with a total of 53 respondents. From the results of the data analysis carried out, it is known that: 1) Motivation has a significant effect on employee performance with a calculated t value of 2.783; 2) Compensation has a significant effect on Employee Performance with a calculated t value of 4.994 and 3) Motivation and Compensation have a significant effect on Employee Performance with a calculated f value of 16.023.